Downfall of pollen carriage by ants after Argentine ant invasion in two Mediterranean Euphorbia species - Blancafort, X; Gómez, C (VIE ET MILIEU-LIFE AND ENVIRONMENT, 2006)
We have studied the influence of Argentine ant invasion on the level of pollen grain carriage by ants in Euphorbia characias and E. biumbellata, two deciduous shrubs visited by ants. The observations were made in two contiguous areas, invaded and non-invaded by the Argentine ant Linepithema humile, in a Mediterranean cork-oak forest. In the invaded area L. humile displaced all native ants that climb to the cyathia of the inflorescences, except Plagiolepis pygmaea, a tiny ant species. Eight native ant species were detected in non-invaded areas. Camponotus cruentatus (52.06 +/- 5.57 pollen grains carried per ant worker of E. characias and 38.84 +/- 6.82 pollen grains of E. biumbellata, mean se) and Camponotus piceus (42.80 +/- 21.57 pollen grains of E. biumbellata) carried much more pollen than L. humile worker ants (0.37 +/- 0.06 pollen grains of E. characias and 0.44 +/- 0.21 pollen grains of E. biumbellata). The Argentine ant and the native ants collected nectar, but C. cruentatus, the visiting ant species most abundant in the non-invaded area, touched the anthers or the stigma of the flowers three times more frequently than the Argentine ant. These results suggest the Argentine ant displace the native ants and that the invasion could interfere with natural visitors or potential pollinators in several plants.
Keywords: Biological invasion; pollen carriage; pollination

Downfall of pollen carriage by ants after Argentine ant invasion in two Mediterranean Euphorbia species - Blancafort, X.; Gómez, C. (VIE ET MILIEU-LIFE AND ENVIRONMENT, 2006)
We have studied the influence of Argentine ant invasion on the level of pollen grain carriage by ants in Euphorbia characias and E. biumbellata, two deciduous shrubs visited by ants. The observations were made in two contiguous areas, invaded and non-invaded by the Argentine ant Linepithema humile, in a Mediterranean cork-oak forest. In the invaded area L. humile displaced all native ants that climb to the cyathia of the inflorescences, except Plagiolepis pygmaea, a tiny ant species. Eight native ant species were detected in non-invaded areas. Camponotus cruentatus (52.06 +/- 5.57 pollen grains carried per ant worker of E. characias and 38.84 +/- 6.82 pollen grains of E. biumbellata, mean se) and Camponotus piceus (42.80 +/- 21.57 pollen grains of E. biumbellata) carried much more pollen than L. humile worker ants (0.37 +/- 0.06 pollen grains of E. characias and 0.44 +/- 0.21 pollen grains of E. biumbellata). The Argentine ant and the native ants collected nectar, but C. cruentatus, the visiting ant species most abundant in the non-invaded area, touched the anthers or the stigma of the flowers three times more frequently than the Argentine ant. These results suggest the Argentine ant displace the native ants and that the invasion could interfere with natural visitors or potential pollinators in several plants.
The following values have no corresponding Zotero field: pub-location: LABORATOIRE ARAGO, BP 44, 66651 BANYULS-SUR-MER CEDEX, FRANCE publisher: OBSERVATOIRE OCEANOLOGIQUE BANYULS
Keywords: Biological invasion; pollen carriage; pollination

Variation for male success in Holm oak, a monoecious and a highly self-incompatible species - Yacine, A; Valero, M; Bouras, F (SEVENTH INTERNATIONAL SYMPOSIUM ON POLLINATION - POLLINATION: FROM THEORY TO PRACTISE, 1997)
In natural populations, male success is determined by pre-and post-pollination events. The latter could be separated to pre-and post-fertilization stages at which different mechanisms control pollen donor success. It is currently assumed that there is a direct relationship between pollen tube growth rapidity and fertilization ability. In this study, pollination experiments were conducted on a Helm oak (Quercus ilex) population to test male success. Pollen was used in two ways (1) as a single source and (2) mixed with the self pollen of the recipient. We analyzed differences between pollen donors at the prezygotic level by evaluating the relative proportions of the pollen tube presence in the style in comparison to those on the stigma and likewise between the style and the ovary, on five different dates after pollination. At the post-zygotic level, male success was measured as the proportion of fertilized ovules relative to pollinated flowers and as seed sired relative to fertilized ovules. At the pre-and post-zygotic level there were statistically significant differences between recipients that are however not significant between donors. In Quercus species pollination occurs before the ovules develop; our results indicate that different arrangements between pollen tube growth and ovule development may occur. Self-incompatibility may be one factor in differential recipient success through the interactions between out and self-incompatible pollen.
Keywords: fertilization; male success; pollen tube; pollination; Quercus ilex

Variation for male success in Holm oak, a monoecious and a highly self-incompatible species - Yacine, A.; Valero, M.; Bouras, F. (SEVENTH INTERNATIONAL SYMPOSIUM ON POLLINATION - POLLINATION: FROM THEORY TO PRACTISE, 1997)
In natural populations, male success is determined by pre-and post-pollination events. The latter could be separated to pre-and post-fertilization stages at which different mechanisms control pollen donor success. It is currently assumed that there is a direct relationship between pollen tube growth rapidity and fertilization ability. In this study, pollination experiments were conducted on a Helm oak (Quercus ilex) population to test male success. Pollen was used in two ways (1) as a single source and (2) mixed with the self pollen of the recipient. We analyzed differences between pollen donors at the prezygotic level by evaluating the relative proportions of the pollen tube presence in the style in comparison to those on the stigma and likewise between the style and the ovary, on five different dates after pollination. At the post-zygotic level, male success was measured as the proportion of fertilized ovules relative to pollinated flowers and as seed sired relative to fertilized ovules. At the pre-and post-zygotic level there were statistically significant differences between recipients that are however not significant between donors. In Quercus species pollination occurs before the ovules develop; our results indicate that different arrangements between pollen tube growth and ovule development may occur. Self-incompatibility may be one factor in differential recipient success through the interactions between out and self-incompatible pollen.
The following values have no corresponding Zotero field: periodical: SEVENTH INTERNATIONAL SYMPOSIUM ON POLLINATION - POLLINATION: FROM THEORY TO PRACTISE issue: 437 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: fertilization; male success; pollen tube; pollination; Quercus ilex